1983
DOI: 10.1007/bf02552975
|View full text |Cite
|
Sign up to set email alerts
|

Venous and nerve invasion as prognostic factors in postoperative survival of patients with resectable cancer of the rectum

Abstract: The histopathologic and clinical findings in 682 patients with carcinoma of the rectum have been analyzed. Invasion of veins and nerves by primary growth was found in 38.9 and 34.9 per cent, respectively. The five-year survival rate for patients with resectable tumors was 49 per cent. The age, Dukes' staging, and presence and/or absence of liver metastases, of venous invasion, and of nerve invasion were found to be of statistically significant importance for the prognosis. Sex was found to be on the borderline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
0
8

Year Published

1988
1988
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(84 citation statements)
references
References 7 publications
3
73
0
8
Order By: Relevance
“…PNI has been recognized in many series as prevalent pathologic features of colorectal cancer and is reported in up to 33% of these tumors at the time resection (Knudsen et al, 1983;Ueno, 2001). In otherwise PNI rate were much higher in pancreatic cancer (70-100%) and 75-85% in biliary tract cancer (Nagakawa et al, 1993;Seki et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…PNI has been recognized in many series as prevalent pathologic features of colorectal cancer and is reported in up to 33% of these tumors at the time resection (Knudsen et al, 1983;Ueno, 2001). In otherwise PNI rate were much higher in pancreatic cancer (70-100%) and 75-85% in biliary tract cancer (Nagakawa et al, 1993;Seki et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of neural, lymphatic and vascular invasion on survival and on the prognosis for colorectal cancer has already been the topic of many researches in the literature 2,12 , and it has been shown that the involvement of these structures is associated with worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…6 ,7 Estudos têm sido publicados correlacionando variáveis clínicas e histopatológicas ao prognóstico do CCR, mas seus resultados são intrigantes e muitas vezes conflituosos. 8 ,9 O diagnósti-co precoce, 10 a idade, 11 localização da neoplasia, 12 graduação histológica, 13 grau de penetração na parede intestinal, 14 comprometimento linfonodal, 15 produção de muco pela neoplasia, 16 antígeno carcinoembrionário (CEA), 17 invasão venosa e neural 18 são as variáveis mais freqüentemente estudadas, como fatores relacionados ao prognóstico da enfermidade. Estudos foram realizados com o intuito de discriminar o poder prognóstico independente das principais variáveis relacionadas ao CCR.…”
Section: Introductionunclassified
“…19 ,20 O consenso dessas publicações revela que os fatores que apresentam associação com a evolução dos doentes são: profundidade de infiltração do tumor na parede intestinal, o comprometimento linfonodal, a presença de metástases e a graduação histológica da neoplasia. 18,19 Entretanto, as tentativas de avaliação prognóstica baseadas puramente em aspectos morfológicos, apresentam a grave limitação de restringirem-se à observação de um registro microscó-pico momentâneo da morfologia tumoral, não fornecendo informações sobre o real comportamento biológico do tumor, o qual se encontra relacionado a mecanismos intrínsecos de funcionamento das células componentes daquele tecido. 19 Recentemente, com a melhor compreensão das alterações genéticas envolvidas na carcinogênese colorretal, a pesquisa de instabilidades de cromossomos e genes, bem como as alterações da expressão tecidual de proteínas por eles codificadas vêm tornando atraente a possibilidade do emprego de fatores funcionais como variáveis potencialmente válidas para a melhor compreensão do prognóstico do CCR.…”
Section: Introductionunclassified